2017
DOI: 10.1049/oap-cired.2017.1074
|View full text |Cite
|
Sign up to set email alerts
|

Ultra fast charging station harmonic resonance analysis in the Dutch MV grid: application of power converter harmonic model

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The transfer ratio from MV to LV was, instead, between 0.5 V/V and 3.0 V/V, while no information was reported for the current transfer ratio. In [44], an advanced converter harmonic model was introduced to study harmonic resonance when an ultra-fast charging station was connected to the MV grid. This model was used for the impedance calculation up to 2.5 kHz.…”
Section: Typical Amplitude and Frequency Of Hfdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer ratio from MV to LV was, instead, between 0.5 V/V and 3.0 V/V, while no information was reported for the current transfer ratio. In [44], an advanced converter harmonic model was introduced to study harmonic resonance when an ultra-fast charging station was connected to the MV grid. This model was used for the impedance calculation up to 2.5 kHz.…”
Section: Typical Amplitude and Frequency Of Hfdsmentioning
confidence: 99%
“…HFD propagation generally depends on the impedance of the LV and MV grids and the connected devices. The sensitivity of HFD propagation to changes of the grid impedance at the delivery point has been modeled for the case of EV chargers connected to a LV DC distribution grid [13] and assessed in two experimental case studies [43,44]. It has been found that HFDs can propagate through transformers, with different transfer ratios depending on the direction of propagation.…”
Section: Propagation Of Hfds: Grid Impedance Measurementmentioning
confidence: 99%
“…The results of harmonic resonance when a DCFC is connected to an MV network are discussed in [156]. Specifically, unacceptable harmonic voltage distortion occurred due to a VSC-based converter and an ultra-fast charger (250 kW × 4) causing a resonance in network impedance in an MV power grid in the Netherlands.…”
Section: Harmonic Distortionsmentioning
confidence: 99%
“…Depending on the characteristics of the respective sources, such emissions may have a varied and peculiar time-frequency and impedance behavior. Paired to the relative difficulty of carrying out comprehensive tests, authors have concentrated mostly on relevant types of sources, such as wind parks [1,2], photovoltaic (PV) parks [3][4][5], electric vehicle (EV) chargers [6][7][8], and smart lighting (e.g. LED or fluorescent lamps) [9,10], including the various cases of lighting as victims and sources of secondary emissions [11,12].…”
Section: Introductionmentioning
confidence: 99%